2009
DOI: 10.1111/j.1468-2982.2008.01755.x
|View full text |Cite
|
Sign up to set email alerts
|

Oestrogen Increases Nociception Through ERK Activation in the Trigeminal Ganglion: Evidence for a Peripheral Mechanism of Allodynia

Abstract: The mitogen-activated protein kinase, extracellular signal-regulated kinase (ERK), is activated in experimental models of chronic pain, and is also activated by oestrogen. We used an established model of inflammatory trigeminal pain, injection of Complete Freund's Adjuvant (CFA) into the masseter muscle, to determine whether ERK activation may play a role in hormone-related trigeminal pain disorders. We measured withdrawal responses to stimulation of the masseter (V3, primary allodynia) and whisker pad (V2, se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
51
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(58 citation statements)
references
References 59 publications
6
51
1
Order By: Relevance
“…Trigeminal nucleus and ganglion, and dura mater tissue samples were isolated as previously described (Liverman, et al, 2009). Western blot analysis was performed for phosphorylated ERK (the activated form) using a 10% resolving SDS-PAGE gel and 5 micrograms of protein were loaded for each sample as previously described (Vermeer, 2014).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Trigeminal nucleus and ganglion, and dura mater tissue samples were isolated as previously described (Liverman, et al, 2009). Western blot analysis was performed for phosphorylated ERK (the activated form) using a 10% resolving SDS-PAGE gel and 5 micrograms of protein were loaded for each sample as previously described (Vermeer, 2014).…”
Section: Methodsmentioning
confidence: 99%
“…It is established that estradiol receptors are present in trigeminal nociceptors and studies have demonstrated that binding of estradiol leads to downstream activation of extracellular signal regulated kinase (ERK), a known inflammatory response pathway (Liverman, et al, 2009). Furthermore, it has been shown that estradiol exposure can lead to other nociceptive-related downstream effects; including, increased primary neuron activity (Cairns, et al, 2001, Cairns, et al, 2002), increased allodynia (Liverman, et al, 2009), altered sodium gated channel activity (Wang, et al, 2013), and enhanced vasodilation (Levy and Burstein, 2011, Sarajari and Oblinger, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…In DRG neurons in vitro, estrogen, acting via ER␣ associated with the plasma membrane, rapidly (with 5 min) reduces ATP-mediated intracellular calcium mobilization (Chaban and Micevych, 2005). Estrogen also rapidly activates extracellular signal-regulated kinase (Liverman et al, 2009) and interferes with exchange protein activated by cAMP-mediated activation of protein kinase Cε (Hucho et al, 2006). These data suggest that estrogen can exert multiple actions (genomic and nongenomic) on primary sensory neurons to regulate pain neurotransmission.…”
Section: Introductionmentioning
confidence: 97%
“…Estrogen receptors (ERs) are expressed in nociceptors of the trigeminal ganglia (TG) and dorsal root ganglia (DRG) (Yang et al, 1998;Bereiter et al, 2005), and treatment with 17␤-estradiol (17␤-E 2 ) influences a variety of functions and cellular processes in nociceptors such as expression of trkA mRNA (Liuzzi et al, 1999), expression of calcitonin generelated peptide mRNA and protein (Gangula et al, 2000), extracellular signal-regulated kinase activity (Liverman et al, 2009), calcium mobilization (Chaban and Micevych, 2005), and transient receptor potential cation channel V1 (TRPV1) function (Xu et al, 2008). Furthermore, local 17␤-E 2 injection into the temporomandibular joint reduces nociceptive behavioral responses to intrajoint administration of formalin (Fá varo-Moreira et al, 2009), suggesting estrogen's effect on nociceptors is functionally relevant.…”
Section: Introductionmentioning
confidence: 99%
“…However, little is known about the contribution of these signaling pathways in mediating rapid effects of estrogen on nociception. In one study, rapid enhancement of inflammation-induced mechanical allodynia of the masseter muscle by estrogen was shown to be mediated by activation of extracellular signal-regulated kinase in sensory neurons (Liverman et al, 2009a). Additional experiments are needed to delineate the signaling pathway(s) regulated by membrane-associated ERa activation that mediates effects of estrogen to enhance BK-stimulated signaling in peripheral sensory neurons.…”
Section: Discussionmentioning
confidence: 99%